PENGARUH SHOPPING LIFESTYLE DAN FASHION INVOLVEMENTTERHADAP IMPULSE BUYING BEHAVIOR MASYARAKAT HIGH INCOME DI FASHION HOUSE 10 TASBIH 1 MEDAN - Ropita Tumangger; Wan Suryani; Teddi Pribadi (Universitas Medan Area, 2020)
The purpose of this study was to determine and analyze the effects of shopping lifestyle and fashion involvement to impulse buying behavior of high income people at fashion house 10 tasbih 1 medan, The research methode used is associtive research, where variables are measurea on a likert scale. The methode of data collection is done by interview (interview), with a list of question (questionnaire) and study documentation. Sampling with saturated sampling method or better known as the census,in this study the number of samples is 89 people. Data processing using SPSS software version 20, with descriptive analysis and hypothesis testing multiple regression analysis.The result showed that : (1) partially shopping lifestyle variables influence to impulse buying at fashion house 10 tasbih 1 medan. (2) partially fashion involvement variables influence to impulse buying at fashion house 10 tasbih 1 medan.. (3) partially simultaneously there is a positive and significant effect between shopping lifestyle and fashion involvement variables effect to impulse buying at fashion house 10 tasbih 1 medan.